AL SAM'U WA AL TĀ'AH FĪ AL ISLĀM: DIRĀSAH AWWALIYYAH - Misnawati, Misnawati; Jamal Elatrash, Radwan (Islam Futura, 2022)
This research deals with a preliminary study for hearing and obedience in the Islam. This research aims to explain the concept hearing and obedience and report the importance of hearing and obedience and types of hearing and obedience. Then discover the effects of hearing and obedience both individually and collectively. And summarizes that the word of hearing in the Quran is still followed to obedience. Hearing and obedience to Allah r and the Messenger of Allāh r is absolute. As for hearing and obedience to guardians, parents, the husband and others, they are restricted to what was known in the Sharia, that is, if they agree to the truth and what they violate, meaning as long as they are not commanded to disobey Allāh, because there is no obedience to a created being in disobedience to the Creator. He who is characterized by this quality has fully enjoyed this life and the hereafter.